HELP ME CHATGPT! WHAT WAYS DOES CHATGPT INFLUENCE STUDENTS' PRODUCTIVITY AND CREATIVITY IN ENGLISH ACADEMIC WRITING? - Sudrajad, Wahyu; Fikri, Moh. Hilman; Putra, Rizky Perdana Bayu (EDUCATUM: Scientific Journal of Education, 2024)
. This study explores the influence of ChatGPT, an AI-powered writing tool, on academic writing among Indonesian university students. Utilizing survey data from 120 participants and qualitative insights from interviews, it examines students' perspectives on ChatGPT's impact on writing productivity, quality, and creativity. Findings indicate that ChatGPT is widely used for organizing ideas and accelerating the drafting process. However, opinions differ regarding its effectiveness in reducing wordiness and maintaining originality. Ethical considerations surrounding plagiarism and the integration of AI in education are scrutinized. While some students appreciate the efficiency and structure ChatGPT provides, others express concerns about over-reliance and diminished personal input. The study highlights the importance of balanced AI integration in education to enhance learning outcomes while fostering critical thinking and ethical reasoning. Recommendations include incorporating discussions on ethical AI use into curricula and conducting further research on long-term impacts and strategies to optimize AI’s educational utility. This research contributes to the understanding of AI's role in academic writing, suggesting pathways to leverage its benefits while mitigating potential drawbacks. By promoting a nuanced approach, it aims to maximize AI’s positive impact on education, ensuring that students not only improve their writing skills but also develop essential critical thinking and ethical awareness. Overall, the study underscores the need for thoughtful integration of AI tools like ChatGPT in academic settings, balancing technological advancements with the cultivation of independent thinking and originality in student work.